From Technological Catch-up to Innovation : The Future of China’s GDP Growth - Yusuf, Shahid (World Bank, Washington, DC, 2013)
This report stats that income gaps among countries are largely explained by differences in productivity. By raising the capital/labor ratio and rapidly assimilating technologies across a wide range of activities, China has increased factor productivity manifold since 1980 and joined the ranks of middle income countries. With the launch of the 12th FYP, China has set its sights on becoming a high income country by 2030 through a strategy combining high levels of investment with rapid advances in technology comparable to that of Japan from the 1960s through the 1970s, and Korea s from the 1980s through the end of the century. The report concludes that the best bet is an innovation system anchored to and drawing its energy from a competitive national economy. Technological progress and the flourishing of innovation in China will be the function of a competitive, globally networked ecosystem constructed in two stages during 2011- 2030. Government technology cum competition policies will provide impetus in the first stage, but success will hinge on the quality of the workforce, the initiative and policies of firms, the emergence of supporting services.